High incidence of esophageal fistula on patients with clinical T4b esophageal squamous cell carcinoma who received chemoradiotherapy: A retrospective analysis. (May 2021) - Chen, Baoqing; Deng, Meiling; Yang, Chen; Dragomir, Mihnea P.; Zhao, Lei; Bai, Kunhao; Xi, Mian; Hu, Yonghong; Zhu, Yujia; Li, Qiaoqiao
Highlights: Satisfactory survival outcomes for T4b ESCC patients with the median OS and 3- year OS rates of 12.2 months and 29.9% was observed in a cohort including 136 patients who were treated with CRT. One third (30.1%) of the patients developed esophageal fistula and those patients that developed fistula had a significantly shorter OS. Tumor ulceration and bronchus/trachea invasion are the two independent risk factors for developing esophageal fistula after CRT in T4b ESCC. Abstract: Background and purpose: Despite definitive chemoradiotherapy (CRT) being a recommended therapeutic method for patients with T4b esophageal squamous cell carcinoma (ESCC), treatment response and complications remain unclear. Esophageal fistula is a severe CRT-related complication when treating locally advanced ESCC, but data on risk factors that lead to esophageal fistula formation are limited. The aim of this analysis is to characterize the outcomes of T4b ESCC treated by CRT and investigate the risk factors of esophageal fistula. Materials and methods: We retrospectively analyzed 136 patients with clinically unresectable T4b ESCC who were treated with CRT. Response, survival, and complication rates, particularly the rate of esophageal fistula and its associated risk factors were analyzed. Results: The median progression-free survival and overall survival (OS) of all patients were 7.9 (95% confidence interval [CI]: 6.1–9.7) and 12.2 months (95% [CI]: 8.9–15.4), respectively. The Kaplan–Meier curves showed that the 3- and 5-year OS rates were 29.9% and 20.2%, respectively. The incidence rate of esophageal fistulas was 30.1%. The median OS for patients with esophageal fistula was only 6.9 (95%[CI] = 6.0–7.8) months. The risk for developing esophageal fistulas was significantly high for ulcerative-type tumors (odds ratio [OR] = 3.202; 95%[CI] = 1.036–7.850, P = 0.011) and for those invading the bronchus/trachea (OR = 3.378; 95%[CI] = 1.223–9.332, P = 0.048). Conclusion: We demonstrated that CRT for T4b ESCC patients has a curative potential, despite a high incidence of esophageal fistula, which was the main cause of treatment failure. The higher risk for fistula formation were tumors with ulceration or bronchus/trachea invasion.